Fatal non-ballistic Penetrating Injury by a Metal Piece from a Rolling Machine: A Case Report (Indian Internet Journal of Forensic Medicine and Toxicology, 2013)
Missile injuries are predominantly caused by firearms, shrapnels during bomb explosions, and so on. Non-ballistic penetrating missile injuries are very rare. In this case, an adult male, while working on a cold stainless steel rolling machine, had sustained a penetrating injury to the outer aspect of upper 1/3rd of left thigh, by a metal piece, ejected from the metal sheet moving on the rolling machine. The metal piece entered the pelvic cavity fatally injuring his visceral organs. He was brought dead on arrival. The case is unique since it is the first reported case of a non-ballistic missile injury that was accidental and fatal. There was also no direct human involvement. In most reported cases of such kind, head injuries are the commonest, and prove to be fatal.
Keywords: Missile; Penetrating; Rolling machine; Pelvic cavity; Non ballistic